Asian and Oceanic Christianities in conversation : exploring theological identities at home and in diaspora - Kim, Hŭb-yŏng, 1949-; Matsuoka, Fumitaka; Morimoto, Anri, 1956- (Studies in world Christianity and interreligious relations ;, 2011)
The old contrast between "universal" and "local" is now collapsing, but a new paradigm has yet to be defined. The contributors claim that the questions they raise will help redraw the lines of demarcation each in a unique way. Their collaborative result is a re-submission of the century-old question regarding "the essence of Christianity," and the readers will hear answers to this question resounding in polyphonic voices. The book will make a unique contribution to the scholarship by constructing a common forum connecting diasporic Asians and Oceanians who live and work in regions around the page.